2014
DOI: 10.1002/pc.23221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization and chemical treatment on the mechanical properties of coir pith/nylon/epoxy hybrid composites

Abstract: The aim of the work was to develop environmental friendly coir pith-based composites with a good balance of mechanical properties. Multilayered coir pith/ nylon fabric/epoxy hybrid composites were fabricated by the hand lay-up technique followed by compression molding. A set of composites of same composition having chemically treated coir pith was also prepared. Mechanical properties of composites such as tensile strength, impact strength, flexural strength, hardness, and abrasion resistance were evaluated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Voids in the composites also decrease considerably after chemical treatments attributable to the increased compatibility. It was suggested that a combination of chemical treatments and hybridization with nylon fabrics was necessary to obtain good mechanical properties .…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voids in the composites also decrease considerably after chemical treatments attributable to the increased compatibility. It was suggested that a combination of chemical treatments and hybridization with nylon fabrics was necessary to obtain good mechanical properties .…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
“…A multilayered coir pith was combined with nylon fabric and epoxy to form hybrid composites with enhanced mechanical properties. Several chemical treatments were also done on the coir pith before incorporating into the composites . Combining (hybridization) of coir pith fibers with nylon increased the mechanical properties up to 73% depending on the number of layers in the composites.…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
“…The hardness of the samples was measured using Rockwell hardness testing machine (Wilson 2000T, Buehler, Lake Bluff, IL, USA) according to ASTM (E18-11) [17]. The abrasion resistance was tested according to ASTM (D1044-08e1) [18,19], using Taber abrasion tester (Messmer 5130, Messmer Instruments Ltd., Kent, UK). Water swelling test of PMMA/SSF nanocomposites was examined according to ASTM (D570-98 e1) [5,19].…”
Section: Experimental Techniquesmentioning
confidence: 99%